Novel synthesis of substituted N-(3-aryl-1, 8-naphthyridin-2-yl) and N, N′-bis(3-aryl-1, 8-naphthyridin-2-yl)benzene-1, 4-diamines and 2-(4-((3-aryl-1, 8-naphthyridin-2-yl)amino)phenyl)isoindoline-1, 3-diones and their biological evaluation. Issue 1 (2nd January 2018) - Ravi, D.; Sakram, B.; Ashok, K.; Rambabu, S.; Sonyanaik, B.; Kurumanna, A.; Madhu, P.
ABSTRACT: A straightforward and highly efficient series of new substituted 3-aryl-1, 8-naphthyridine derivatives3a–e, 4a–e, and6a–e were synthesized. Condensation dissimilar quantities of 2-chloro-3-aryl-1, 8-naphthyridine1a–e with benzene-1, 4-diamine2 and sodium ethoxide refluxing in ethanol solvent yielded the compounds3a–e and4a–e . The 2-(4-((3-aryl-1, 8-naphthyridin-2-yl)amino)phenyl)isoindoline-1, 3-diones6a–e were obtained by treatment of compounds3a–e with phthalic anhydride5 in refluxing N, N -dimethylformamide is described. All synthesized compounds evaluated for their antimicrobial activity. The structures of the compounds have been proven on the established of spectral (IR, 1 H NMR, and 13 C NMR) data and elemental analyses. The reaction will be characterized by good efficacy, easy workup, simple purification of the products, and availability of catalyst. GRAPHICAL ABSTRACT: